Screening of individuals of age group 25 years and above for hypertension and diabetes in urban slum community, Sion, Mumbai - Kadam, Deepali Mohan; Kowli, Shobha; Mali, Satish (International Journal Of Community Medicine And Public Health, 2017)
Background: The prevalence of hypertension and diabetes is showing an increasing trend. In India, majority of individuals are not aware of presence of these conditions in self, as they do not undergo regular health checkups. Majority are diagnosed when they undergo routine investigations for surgical procedures or medical examination for some other health problem. These conditions can be detected early, by simple screening techniques such as measuring blood pressure and blood sugar level which can be carried out by trained individuals, leading to reduction in the morbidity and mortality. Hence an initiative was taken to identify and train adolescent volunteers from the community to educate and screen the individuals of urban slum area Pratikshanagar, Sion, Mumbai. Objectives of the study were to screen individuals ≥25 years of age for hypertension and diabetes; to find the level of risk factors like alcohol, tobacco consumption, obesity. Methods: It is a cross – sectional type of study. Results: Out of 1119 individuals, 113 (10.09%) were aware of their hypertensive status, thus from the rest 1006 individuals screened, 147 (14.61%) were detected with raised blood pressure. Out of these 147, 86 (8.54%) were confirmed as hypertensive. With regards to diabetes, out of 1119 individuals, 82 (7.32%) were aware of their diabetic status. On screening the rest 1037, 23 (2.21%) were detected with raised blood sugar. Out of these 23, 13 (1.25%) were confirmed as diabetics. Conclusions:Volunteers from community can be trained for screening individuals in their locality thus ensuring early detection of hypertension and diabetes.